Estimated Economic Losses of Farmer Households Due to Batanghari River Flooding in Pulau Kayu Aro Village, Sekernan Subdistrict, Muaro Jambi Regency - Nurul Iqamah Elza; Rahmi Hidayati; Vika Indah Rahayu; Dwi Arianti; Rizky Saputra (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
Flooding is the most dominant natural disaster in Indonesia and has significant impacts on the socio-economic lives of communities, including farming households living around river basins (watersheds). One of the areas that experiences recurrent flooding is Pulau Kayu Aro Village, Sekernan District, Muaro Jambi Regency, which is located in the Batanghari Watershed. This study aims to estimate the economic losses of farming households caused by flooding. The research employed a descriptive quantitative and qualitative approach using a survey method on 50 flood-affected farming households selected purposively. Primary data were obtained through interviews using questionnaires, while secondary data were collected from relevant institutions. The estimation of economic losses was calculated based on direct and indirect losses. Direct losses include repair, damage, and replacement costs, while indirect losses cover prevenion costs, medical expenses, loss of income, and additional costs. The results show that the total economic loss of farming households in Pulau Kayu Aro Village reached IDR 1,345,776,900, with the largest contribution coming from indirect losses amounting to IDR 904,460,700, while direct losses amounted to IDR 441,316,200. The dominance of indirect losses indicates that the impacts of flooding are not only physical but also create sustained economic pressure on farming households. The government has undertaken various efforts to reduce the impacts of flooding in Pulau Kayu Aro Village through both structural and non-structural approaches. The River Basin Agency (BWS) VI Sumatra has constructed river embankments along the Batanghari Watershed, the Regional Disaster Management Agency (BPBD) of Muaro Jambi Regency has improved preparedness through socialization, water level monitoring, and disaster response coordination, and the Environmental Agency of Muaro Jambi Regency supports flood mitigation through upstream reforestation, controlling environmentally damaging activities, and waste management. Synergy among institutions is a key factor in reducing flood risk and enhancing community resilience. Therefore, these findings are important as a basis for developing mitigation strategies, planning economic recovery, and formulating policies for the protection and empowerment of farming households in the study area. This study emphasizes the importance of strengthening integrated flood mitigation strategies, both structural and non-structural, to reduce the economic losses of farming households.